2013
DOI: 10.1007/s10461-013-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Fataki Campaign: Addressing Cross-Generational Sex in Tanzania by Mobilizing Communities to Intervene

Abstract: The national multimedia "Fataki" campaign aired in Tanzania from 2008 to 2011 with the goal of addressing cross-generational sex (CGS) by mobilizing communities to intervene in CGS relationships. A cross-sectional household survey was used to evaluate the campaign. Logistic regression analysis found a dose-response relationship between campaign exposure and interpersonal communication about CGS, intervening in CGS relationships, and lower CGS engagement among women. No association was found between campaign ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It likewise ignores the existence of multiple masculinities, the diversity of men's sexuality (Shefer and Strebel 2012;Barker 2005) and the intersection of masculinities with variables such as socio-economic status and age (Dworkin, Fleming, and Colvin 2015). Evaluation of efforts to reduce transactional sex in South Africa and Tanzania have shown little effectiveness (Kaufman et al 2016;Van der Heijden and Swartz 2014;Kaufman et al 2013;Brouard and Crewe 2012), which highlights the risks of both framing men as a homogenous group, and adopting shaming and punitive approaches to working with men and adolescent boys.…”
Section: Introductionmentioning
confidence: 99%
“…It likewise ignores the existence of multiple masculinities, the diversity of men's sexuality (Shefer and Strebel 2012;Barker 2005) and the intersection of masculinities with variables such as socio-economic status and age (Dworkin, Fleming, and Colvin 2015). Evaluation of efforts to reduce transactional sex in South Africa and Tanzania have shown little effectiveness (Kaufman et al 2016;Van der Heijden and Swartz 2014;Kaufman et al 2013;Brouard and Crewe 2012), which highlights the risks of both framing men as a homogenous group, and adopting shaming and punitive approaches to working with men and adolescent boys.…”
Section: Introductionmentioning
confidence: 99%
“…MYSA youth were more likely to report condom use during their first and last sexual encounters, but there were no other impacts on sexual behaviour in this study (Delva et al, 2010) or in Regai Dzive Shiri (Cowan et al, 2010). Women who had been exposed to the Fataki campaign were less likely to be involved in cross-generational relationships, although there was no association between intervention exposure and involvement in crossgenerational relationships among men (Kaufman et al, 2013a). Only the Regai Dzive Shiri intervention measured clinical outcomes and found that young women in the intervention were less likely to report ever being pregnant, but there were no other impacts on HIV, HSV-2 or current pregnancy (Cowan et al, 2010).…”
Section: Social Normsmentioning
confidence: 59%
“…Youth involved in the MYSA, compared to youth from youth clubs, schools and social organizations in the same areas, did not differ in terms of gendered subjective norms on virginity, responsibility or fidelity; behavioural attitudes towards risk-avoiding behaviour; or behavioural intentions concerning condom use (Delva et al, 2010). The Fataki campaign increased discussion about cross-generational sex and willingness to intervene to challenge such relationships but did not shift social norms to oppose such relationships, although the evaluation did not report results for participants under age 24 (Kaufman et al, 2013a).…”
Section: Social Normsmentioning
confidence: 88%
See 1 more Smart Citation
“…For more than a quarter century, transactional sex has been implicated in the disproportionately high rates of HIV infection affecting adolescents and young adults in sub-Saharan Africa, especially for girls and young women (Dahl, 2015; George et al, 2019; Hoss & Blokland, 2018; Kaufman et al, 2013; Leclerc-Madlala, 2008; Luke, 2005; Mavhu et al, 2017; Moodley & Ebrahim, 2019; Nkosana & Rosenthal, 2007a, 2007b; Nobelius et al, 2010, 2011; Ranganathan et al, 2018; Selikow & Mbulaheni, 2013; Silberschmidt & Rasch, 2001; Tener, 2021; Wyrod et al, 2011). Transactional sex refers to adult-initiated informal sexual exchange with adolescents in return for providing them material goods such as clothes, money, access to mobile phones, and transport.…”
mentioning
confidence: 99%